Hydrogen sulfide and polysulfides induce GABA/glutamate/d-serine release, facilitate hippocampal LTP, and regulate behavioral hyperactivity - Hiroki Furuie; Yuka Kimura; Tatsuhiro Akaishi; Misa Yamada; Yoshiki Miyasaka; Akiyoshi Saitoh; Norihiro Shibuya; Akiko Watanabe; Naoki Kusunose; Tomoji Mashimo; Takeo Yoshikawa; Mitsuhiko Yamada; et al. (Scientific Reports, 2023)
Abstract Hydrogen sulfide (H2S) and polysulfides (H2Sn, n ≥ 2) are signaling molecules produced by 3-mercaptopyruvate sulfurtransferase (3MST) that play various physiological roles, including the induction of hippocampal long-term potentiation (LTP), a synaptic model of memory formation, by enhancing N-methyl-d-aspartate (NMDA) receptor activity. However, the presynaptic action of H2S/H2Sn on neurotransmitter release, regulation of LTP induction, and animal behavior are poorly understood. Here, we showed that H2S/H2S2 applied to the rat hippocampus by in vivo microdialysis induces the release of GABA, glutamate, and d-serine, a co-agonist of NMDA receptors. Animals with genetically knocked-out 3MST and the target of H2S2, transient receptor potential ankyrin 1 (TRPA1) channels, revealed that H2S/H2S2, 3MST, and TRPA1 activation play a critical role in LTP induction, and the lack of 3MST causes behavioral hypersensitivity to NMDA receptor antagonism, as in schizophrenia. H2S/H2Sn, 3MST, and TRPA1 channels have therapeutic potential for psychiatric diseases and cognitive deficits.